Comparison of three simple methods for the assessment of `free' thyroid hormone - Gimlette, T. M. D. (1967)
A dialysis method for estimating `free' thyroxine is compared with two indirect methods using the uptake of triiodothyronine by the red cells and by a Sephadex column. The three methods give results which correlate well and the Sephadex method is the simplest. The theoretical basis of such tests and their role in the assessment of thyroid status is briefly discussed.